The Influence Mechanism of Learning Orientation on New Venture Performance: The Chain-Mediating Effect of Absorptive Capacity and Innovation Capacity - Yang, Yanling; Zheng, Yanling; Xie, Guojie; Tian, Yu (Frontiers in Psychology, 2022)
New ventures have stronger learning motivation but higher failure rates. In the era of the digital economy, it is necessary to clarify whether and how learning orientation gives scientific guidance for new ventures. We developed a chain multiple intermediary model following the paradigm of "orientation capability performance", which was empirically analyzed using data from 214 Chinese new ventures. The results show that learning orientation not only has a direct positive impact on new venture performance but also has an indirect positive effect through the chain mediating effect of absorptive capacity and innovation capacity.  The study advances theoretical understanding of the effect and path of learning orientation on new venture performance, fosters in-depth research on organizational learning and dynamic capability, and provides targeted organizational learning solutions for new ventures in emerging economies.